A study of the adequacy of laws relating to the management of residential stratified properties in peninsular Malaysia - Mazliza Mohamad (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2015)
This thesis examines the adequacies of the existing legal framework regulating the management of the stratified properties in Peninsular Malaysia. It identifies the inadequacies and legal developments towards proposing improvement to the existing system. The research adopts a qualitative research by using the doctrinal research method. Legislations on management of the stratified properties in Singapore and New South Wales, Australia are taken as a benchmark to compare the previous and current Malaysian laws on stratified property management. The thesis concludes with the findings that the introduction of the Strata Management Act 2013 is clear and comprehensive to overcome the weaknesses in the legal framework of the stratified property management provided in the Building and Common Property (Maintenance and Management) Act 2007.